Direct fermentation of potato starch and potato residues to lactic acid by Geobacillus stearothermophilus under non‐sterile conditions. Issue 4 (29th January 2015) - Smerilli, Marina; Neureiter, Markus; Wurz, Stefan; Haas, Cornelia; Frühauf, Sabine; Fuchs, Werner
Abstract BACKGROUND Lactic acid is an important biorefinery platform chemical. The use of thermophilic amylolytic microorganisms to produce lactic acid by fermentation constitutes an efficient strategy to reduce operating costs, including raw materials and sterilization costs. RESULTS A process for the thermophilic production of lactic acid by Geobacillus stearothermophilus directly from potato starch was characterized and optimized. Geobacillus stearothermophilus DSM 494 was selected out of 12 strains screened for amylolytic activity and the ability to form lactic acid as the major product of the anaerobic metabolism. In total more than 30 batches at 3–l scale were run at 60 °C under non‐sterile conditions. The process developed produced 37 g L−1 optically pure (98%) L‐lactic acid in 20 h from 50 g L−1 raw potato starch. As co‐metabolites smaller amounts (<7% w/v) of acetate, formate and ethanol were formed. Yields of lactic acid increased from 66% to 81% when potato residues from food processing were used as a starchy substrate in place of raw potato starch. CONCLUSIONS Potato starch and residues were successfully converted to lactic acid by G. stearothermophilus. The process described in this study provides major benefits in industrial applications and for the valorization of starch‐rich waste streams. © 2015 The Authors.Journal of Chemical Technology & Biotechnology published by John Wiley & Sons Ltd on behalf of Society of Chemical Industry.